Novel approach in the formulation of the geometric relationship between the 3 dimensional body form and the 2 dimensional patterns in establishing a satisfactory fit for ladies' garment - (:unkn) unknown (Textile Inst, Manchester, United Kingdom, 1997)
A geometric approach is developed to establish the relationship between the three-dimensional constitution of the body and two-dimensional pattern forms, including the important depth and breadth measurements used in patternmaking. Three steps are taken into consideration: (1) establishing the 3-D coordinates of the body; (2) setting up a 3-D geometric model for the apparel; and (3) breaking up this 3-D model into a 2-D pattern form. A computer program is utilized to calculate the half circumference describing the half widths of breast, waist and hip of the bodice. The program also gives the full widths, depths, and circumference of separate conic sections.